The reproductive aspect of tiny scale barb, Thynnichthys thynnoides (Bleeker, 1852) at Rui River, Perak, Malaysia - Alya Ilyani Abd Malek; Rohasliney Hashim; Zarul Hazrin Hashim (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study aims to understand the reproductive biology of Thynnichthys thynnoides at Rui River, Perak, Malaysia. A total sample of 175 individuals, including 83 from Kuala Rui (S1) and 92 from Air Ganda (S2), were collected from local artisanal fishers. Fish was caught using gill nets and scoop nets during migration and spawning seasons (i.e., November to December 2018). For each fish individual, the total length (TL), body weight (BW), and ovary weight (OW) were and. A Chi-square test was performed to evaluate the sex ratio of the studied population. Simple linear regression analysis was used to explain the relationship between absolute fecundity (FA) or relative fecundity (FR) with total length, body weight, and ovary weight. For a coefficient of determination (r2) and correlation coefficient (r), a regression equation was determined. The results showed that the TL of T. thynnoides varied from 13.3 to 20.3 cm, with a calculated mean of 16.78 ± 1.1 cm. Body weights ranged from 31.86 to 78.86 g, with an average body weight of 53.81 ± 10.1 g. The FA ranged from 14454 to 29531 (mean = 21112 ± 4612) eggs per fish, and the FR from this study ranged from 211 to 658 (mean = 358 ± 93), where the OW was more significantly correlated with the absolute fecundity (r>0.513; p<0.001) than other body metrics. Negative allometric growth of T. thynnoides was observed during this study. The overall ratio of the T. thynnoides was 1:0.82 (male: female). In conclusion, this study has shown that the fecundity of the fish population is declining, although the cause is still unclear. The knowledge of this study would help fisheries managers plan necessary regulations for sustainable fishery practice at the Rui and Perak rivers, specifically during the migration and spawning season of T. thynnoides.